AKTIVITAS BERMAIN ESKA (ESTAFET ANGKA) UNTUK MENGEMBANGKAN MOTORIK KASAR ANAK - Ati’ Mirfaqoh (incrementapedia, 2020)
This research is motivated by activities that rarely pack the learning in the form of games, so the child will only struggle with the child work sheet provided by the teacher only. Thus the purpose of this study was to determine the relationship between gross motor skills in children aged 4-5 years with the activity of playing ESKA. The method used is quantitative method using experimental research design with product moment correlation technique with sample size 20 children aged 4-5 years. The data collection technique used is performance observation with correlation performance test instrument. Data analysis technique used is correlation test. From the results of the analysis through the correlation test obtained that r-count (0,863) and r-table (0,444) at α 5%. Thus r-count > r-table so that (H0) is rejected and (H1) accepted.